Use of Palm Oil Medium (Elaeis guineensis Jacq) in Pre-Nursery Solid Application - Apriyanto, Mulono; Marlina, Marlina; Fikri, KMS Novyar Satriawan; Nursida, Nursida (Akademi Komunitas Perkebunan Yogyakarta, 2024)
The objective of the research is to determine the impact of solid application on the growth of oil palm seedlings and to identify the optimal dosage for promoting their growth in the main nursery. From June to October of 2022, the research was carried out at the Islamic University of Indragiri's Agriculture Faculty's experimental farm. The investigation was conducted using a completely randomised design (CRD) with six treatments: no solid, 150 g/polybag, 200 g/polybag solid, 250 g/polybag solid, 300 g/polybag solid and 350 g/polybag solid used. Each treatment was replicated three times. The collected data were subjected to a 5% level Duncan Multyple Range Test after being statistically analysed using analysis of variance. The findings demonstrated a strong relationship between solid application in oil palm medium and the height of the seeds, the number of leaves, the diameter of the hump, and the dry weight of the oil palm seedlings. The optimal dosage for promoting oil palm seedling growth in pre-nursery is 300 grammes per polybag, applied in a solid form